Brunswickgrass (Paspalum nicorae): A Weed Contaminant in Southern Pastures and Bahiagrass Seed Production Fields - Ann Blount; Marcelo Wallau; Brent Sellers; Dennis Hancock; Leanne Dillard; Jose Dubeux; Cheryl Mackowiak; João Vendramini; Clay Cooper (EDIS, 2022)
This publication provides information on the identification, biology, and management of brunswickgrass. Written by Ann Blount, Marcelo Wallau, Brent Sellers, Dennis Hancock, Leanne Dillard, Jose Dubeux, Cheryl Mackowiak, Joao Vendramini, and Clay Cooper, and published by the UF/IFAS Agronomy Department, revised January 2022.